1999
DOI: 10.1002/(sici)1097-4679(199910)55:10<1271::aid-jclp8>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Frost Multidimensional Perfectionism Scale in a clinical anxiety disorders sample

Abstract: The purpose of this study was to examine the factor structure of the Frost Multidimensional Perfectionism Scale (MPS‐F; Frost, Marten, Laharte, & Rosenblate, 1990). Although perfectionism is thought to contribute to the development of psychopathology and the MPS‐F is gaining popularity for use in assessing perfectionism in clinical samples, to date the factor structure has not been examined in a clinical sample. Three hundred and twenty‐two individuals diagnosed with an anxiety disorder using the SCID for DSM‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 29 publications
(30 reference statements)
7
70
0
6
Order By: Relevance
“…Factor analytic studies investigating the dimensionality of Frost et al's model, however, consistently found fewer than six dimensions (Purdon, Antony, & Swinson, 1999;Cox, Enns, & Clara, 2002) with the majority of studies suggesting that four dimensions-combining concern over mistakes and doubts about actions to one dimension, and parental expectations and parental criticism to one dimension-best capture the dimensionality of the model (Harvey, Pallant, & Harvey, 2004;Stöber, 1998;.…”
Section: Multidimensional Perfectionismmentioning
confidence: 99%
“…Factor analytic studies investigating the dimensionality of Frost et al's model, however, consistently found fewer than six dimensions (Purdon, Antony, & Swinson, 1999;Cox, Enns, & Clara, 2002) with the majority of studies suggesting that four dimensions-combining concern over mistakes and doubts about actions to one dimension, and parental expectations and parental criticism to one dimension-best capture the dimensionality of the model (Harvey, Pallant, & Harvey, 2004;Stöber, 1998;.…”
Section: Multidimensional Perfectionismmentioning
confidence: 99%
“…The original version of FMPS 1 presents six dimensions, but this factor structure was not always replicated. Purdon et al 14 found a three factor solution in a sample of anxiety disorders, and other researchers found four factor solutions [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 97%
“…Por ejemplo, el reactivo 4 que originalmente pertenecía al factor Estándares Personales se agrupa en el factor Preocupación por los Errores (Franco et al, 2010;Purdon et al, 1999). En tanto que los reactivos 6, 12, 16 y 34 de manera consistente han resultado inestables debido a que en ocasiones se agrupan y en otras no cumplen con el criterio de carga factorial establecido.…”
Section: Discussionunclassified